Characterisation of slug flow conditions in pipelines for fatigue analysis - Reda, Ahmed; Forbes, Gareth; Sultan, Ibrahim (Volume 4: Pipeline and Riser Technology, 2011)
Understanding the problem of slug flow induced fatigue damage is of particular importance to the reliable operation of pipelines. Slug flow across unsupported pipeline spans, pipeline crossings or vertical engineered buckle initiators, i.e. sleepers, produces dynamic motion in the pipeline resulting in cyclic fatigue stresses. In some cases, the dynamic effects will cause the pipeline to fail at a point of stress concentration. In other cases, however, these effects may be negligible. The current literature provides no guidance as to when the dynamic effects of slug flow must be considered. This paper gives guidance and describes how fatigue due to slug flow in pipelines, which would normally require dynamic analysis, can be quantified using simplified quasi-static analysis. The paper also presents a design process which could be used by pipeline engineers to determine the level of analysis needed, before embarking on more complex and expensive dynamic finite element. Copyright © 2011 by ASME.